Dl-3-n-butylphthalide inhibits platelet activation via inhibition of cPLA2-mediated TXA2 synthesis and phosphodiesterase. (17th November 2015) - Ye, Jianqin; Zhai, Lili; Zhang, Shenghui; Zhang, Yan; Chen, Leilei; Hu, Liang; Zhang, Si; Ding, Zhongren
Abstract: Aberrant platelet activation plays a critical role in the pathogenesis of heart attack and stroke.dl -3- n -butylphthalide (NBP) has been approved in China to treat stroke with multiple mechanisms. The anti-stroke effects of NBP may be related to its antiplatelet effects reported in rats in addition to its antioxidative, antiapoptotic, and angiogenic effects. However, the effects and the underlying mechanisms of NBP on human platelets are not yet clear. In this study, we found that NBP concentration-dependently inhibited human platelet aggregation and ATP release induced by ADP, thrombin, U46619, arachidonic acid, or collagen. NBP also inhibited PAC-1 binding induced by ADP or thrombin and platelet spreading on immobilized fibrinogen. NBP reduced TXA2 synthesis induced by thrombin or collagen via inhibiting cPLA2 phosphorylation, concomitantly with a marked decrease in intracellular calcium mobilization. Moreover, NBP also inhibited human platelet phosphodiesterase (PDE) and elevated 3, 5-cyclic adenosine monophosphate level in platelets. In conclusion, NBP significantly inhibits human platelet activation via inhibition of cPLA2-mediated TXA2 synthesis and PDE, and may be effective as an antiplatelet drug to treat other arterial thrombotic diseases.